The Role Of Family Functions On The Quality Of Life Of Type 2 Diabetes Mellitus Patients In Primary Service Facilities Of PUSKESMAS Medan Johor - Ali Napiah Nasution; Novia Novia; Suhartina Suhartina (CV. Inara, 2025)
The global focus on non-communicable diseases (NCDs) has been growing, particularly chronic degenerative diseases such as Diabetes Mellitus (DM), which is now a serious threat to public health worldwide. According to WHO data from 2008, these diseases account for 55% of total deaths in Southeast Asia. In Indonesia, the prevalence of type 2 DM has significantly increased, with over 10 million sufferers aged 20-79 years in 2017, making it a significant health management challenge. To address this, BPJS Health launched the Chronic Disease Management Program (Prolanis) to optimize patients' quality of life while maintaining healthcare cost efficiency. Families play a crucial role in supporting DM patients in managing their disease effectively, socially, and in healthcare. This study aims to analyze the relationship between family functioning and the quality of life of type 2 DM patients at the Medan Johor Public Health Center (Puskesmas). Using a cross-sectional study design, data were collected through the WHOQOL-BREF questionnaire to measure quality of life and the Family APGAR questionnaire to assess family functioning. The results showed that most respondents were women, had a high school education, and had been suffering from type 2 DM for less than 10 years. Most family functions were classified as highly functional. Still, no significant relationship was found between APGAR scores and quality of life in the four domains (physical health, psychological, social relationships, and environment).